Long-term effects of lime and phosphogypsum application on tropical no-till soybean-oat-sorghum rotation and soil chemical properties - da Costa, Claudio Hideo Martins [UNESP]; Crusciol, Carlos Alexandre Costa [UNESP] (Elsevier, 2016)
Root growth, nutrition and crop yield can be affected by soil chemical modifications caused by superficial limestone and phosphogypsum application in a no-till system. Using this approach, this study was conducted in southeastern Brazil, continuing an experiment that has been on-going since 2002 with the objective of evaluating the residual effects of the surface application of lime and phosphogypsum on the soil chemical characteristics and the root growth, nutrition and yield of soybean, black oat and sorghum in a dry winter region cultivated in 2008/2009 and 2009/2010. The experimental design was a randomized block with 4 replications. The treatments were applied in November 2004 and were as follows: original conditions, limestone application (2000kgha-1), phosphogypsum application (2100kgha-1), and limestone (2000kgha-1)+phosphogypsum (2100kgha-1) application. Superficial liming with or without phosphogypsum reduced the surface and subsurface soil acidity 5 years after application in the no-till system. The movement of Ca2+ and Mg2+ from the surface layer into the subsoil over time was evident. The phosphogypsum application associated with liming increased the Ca2+ levels throughout the soil profile. Liming maintained high levels of Mg2+ throughout the soil profile with or without phosphogypsum application. The organic matter content increased with liming with or without phosphogypsum, indicating that in the long term, these practices can increase the C accumulation. Phosphogypsum application had a residual effect on the SO4-S levels, and high sulphate concentrations were observed in the subsoil after 5 years. Superficial liming improved crop nutrition and, when associated with phosphogypsum, increased Ca absorption by soybean and sorghum, as reflected in the increased yields of these crops.
Keywords: Avena strigosa; Brazilian tropical soils; Glycine max; Soil conditioner; Soil corrective; Sorghum bicolor